Hedonic impacts of gains versus losses of time: are we loss averse?. Issue 5 (4th July 2021) - Mukherjee, Sumitava; Srinivasan, Narayanan
ABSTRACT: A large part of our daily activities involves judging the psychological value of time. This study tested a previously less explored aspect about whether people are loss averse for time – i.e. do losses of time loom larger than corresponding gains? Using comparative hedonic judgments, the impact of prospective gains versus losses of time was examined for common contexts like waiting and local travel based on suggestions by typical navigation apps. The magnitude of time was varied without an explicit reference point (experiment 1) and with a clear reference without any overt consequence (experiment 2). The contextual nature of outcome along with magnitude was also manipulated (experiment 3). Prospective gains loomed as larger or equal to losses for low magnitudes while there was a trend of losses to loom larger than gains only for high magnitudes of time. These results weaken the empirical evidence for loss aversion and highlight its magnitude-dependent nature thus presenting a nuanced perspective to the affective psychology of time.